2015
DOI: 10.1159/000368073
|View full text |Cite
|
Sign up to set email alerts
|

Stent Thrombosis with Biodegradable Polymer Drug-Eluting Stents versus Durable Polymer Sirolimus-Eluting Stents: An Update Meta-Analysis

Abstract: Objective: Durable polymer sirolimus-eluting stents (DP-SES) are associated with a low risk of stent thrombosis; biodegradable polymer drug-eluting stents (BP-DES) were designed to reduce these risks. However, their benefits are still variable. Method: We undertook a meta-analysis of randomized trials identified by systematic searches of Medline, Embase, and the Cochrane Database. Results: Eleven studies (9,676 patients) with a mean follow-up of 22.6 months were included. Overall, compared with DP-SES, BP-DES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Presently, stent thrombosis in second or third generation stents is a rare clinical scenario [ 23 ]. Also, as confirmed in several meta-analyses BP-DES compared with DP-DES are associated with a lower rate of very late stent thrombosis and an equivalent risk of MACE [ 24 , 25 ]. This probably might be associated with the fact that over time, the drug-coated polymers of BP-DES can gradually degrade into completely harmless CO 2 and H 2 O molecules that are excreted from a patient’s body.…”
Section: Discussionmentioning
confidence: 90%
“…Presently, stent thrombosis in second or third generation stents is a rare clinical scenario [ 23 ]. Also, as confirmed in several meta-analyses BP-DES compared with DP-DES are associated with a lower rate of very late stent thrombosis and an equivalent risk of MACE [ 24 , 25 ]. This probably might be associated with the fact that over time, the drug-coated polymers of BP-DES can gradually degrade into completely harmless CO 2 and H 2 O molecules that are excreted from a patient’s body.…”
Section: Discussionmentioning
confidence: 90%
“…At last, several meta-analysis have compared BP-DES with durable polymer DES [ 34 , 35 ], however, this is the first meta-analysis till date to compare the cardiovascular outcomes in DM versus non-DM participants who were treated with BP-DES.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed BP-DES to be more effective in reducing MACEs and ST than DP-DES during the long term. [ 25 ] Even the study published by Zhu et al [ 26 ] showed BP-DES to be associated with a lower rate of very late ST. However, the authors suggested further studies to confirm their findings.…”
Section: Discussionmentioning
confidence: 99%